HUBUNGAN TINGKAT DEMENSIA DENGAN TINGKAT KEMAMPUAN AKTIFITAS DASAR SEHARI-HARI (ADS) PADA LANJUT USIA DI DESA SUANAE DAN DESA FATUNISUAN KECAMATAN MIOMAFFO BARAT TAHUN 2020 - KRISTINA AQUILINA NAHAK; ROMIDA SIMBOLON (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
According to the World Health Organization (WHO), the elderly is someone who has entered the age of 60 years and over. Elderly is an age group in humans who have entered the final stages of the phase of life. NTT's population growth rate per year (2010-2020) is 1.25%. This data decreased compared to the period 2000-2010 which amounted to 2.07%, the percentage of the population of NTT, productive age (15-64 years) This number increased when compared to 2010 which was 7.5%. The percentage of the elderly population in NTT Province is 9.4%. This is an increase, up compared to the year 2010 which was 7.5%. (BPS, 2019). Based on the survey that has been conducted, researchers will examine the relationship between the level of dementia and the level of ability of basic daily activities in the elderly in Suanae Village and Fatunisuan Village, West Miomaffo District. Based on the survey that has been conducted, researchers will examine the relationship between the level of dementia and the level of ability of basic daily activities in the elderly in Suanae Village and Fatunisuan Village, West Miomaffo District. This research is a non-experimental research using a correlational research design with a cross sectional approach. This research took place in Suanae Village and Fatunisuan Village. The time of the research was carried out in May-June 2020. The population in this study were all elderly people living in Sauane Village and Fatunisuan Village in 2020. The sampling technique in this study was purposive sampling or often also called judgment sampling with a sample of 95 elderly. The result of the study is that the P value is equal to p value < = 0.05, meaning that there is a significant relationship between the level of dementia and basic daily activities. While the OR value is 2.687, meaning that the elderly with severe dementia will be 2.6 times greater for activities. daily basis depends on weight. It is necessary to improve the existing elderly gymnastics program, both in its implementation and in motivating the elderly.